If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4X + 6 + X + 3X = 44 + -2X Reorder the terms: 6 + 4X + X + 3X = 44 + -2X Combine like terms: 4X + X = 5X 6 + 5X + 3X = 44 + -2X Combine like terms: 5X + 3X = 8X 6 + 8X = 44 + -2X Solving 6 + 8X = 44 + -2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2X' to each side of the equation. 6 + 8X + 2X = 44 + -2X + 2X Combine like terms: 8X + 2X = 10X 6 + 10X = 44 + -2X + 2X Combine like terms: -2X + 2X = 0 6 + 10X = 44 + 0 6 + 10X = 44 Add '-6' to each side of the equation. 6 + -6 + 10X = 44 + -6 Combine like terms: 6 + -6 = 0 0 + 10X = 44 + -6 10X = 44 + -6 Combine like terms: 44 + -6 = 38 10X = 38 Divide each side by '10'. X = 3.8 Simplifying X = 3.8
| 5c+3b-3c-3b+2a= | | 10y^3-15y^2-45y=0 | | 0.1x^2+145+8379= | | 4x-7=51 | | 5(2.2+3.7)= | | 2y=5x-2 | | -x^2+9x-112=0 | | -2(n+3)-a=0 | | 5x-10=25x+15 | | 70-3x=15x+18 | | 3x^2+2x-16=16-2x | | 4b^2=17b+15 | | 2x=5y-2 | | -6x+18=-4x+10 | | 2x^2-7x+3=8 | | m^2-6m=-9 | | x+(11+x)=37 | | 5b^2-26b=24 | | 6b+4a=32 | | 12-7x=62-42x | | -6x-15=-5x-8 | | 13-10x=81-24 | | 6x+19=5x+18 | | f(4)=9x^4-8x^2+9x-5 | | 0=-65x-25 | | 4(4k+2)-8(k-2)=3(2k+1)-2 | | x-(6+2)=-6-x | | 6a+4b=32 | | 2x-3=-6+3x | | 9d+2=3d-6 | | x+3x+14=106 | | 18x+4=40 |